The Effect of Plyometric and Extensive Interval Training Methods on the Accuracy of Jumping Smash Athletes of the Badminton Association of Padang City - Muharsyad Al Azip; Syamsuar Syamsuar; Syafruddin Syafruddin; Masrun Masrun (JUARA : Jurnal Olahraga, 2023)
This study aims to determine the effect of pliometrik training methods and extensif intervals on increasing the accuracy of the jumping smash of PB Reta Utama athletes in Padang City. This study uses an experimental method with a "two groups pretest-posttest design" design. the sampling technique used purposive sampling, so the sample of this study was 12 male athletes. The jumping smash accuracy instrument uses a smash accuracy test. The data analysis technique used t-test with a significance level of 5%. The results showed that (1) there was a significant effect of the pliometrik training method on the accuracy of badminton jumping smash in PB Reta Utama athletes in Padang City (2) There was a significant effect of the extensif interval training method on the accuracy of badminton jumping smash in athletes of PB Reta Utama Kota. Padang (3) The extensif interval training method is better than the pliometrik training method in the accuracy of badminton jumping smash in PB Reta Utama athletes in Padang City, with a posttest average difference of 3.33.